Alternative yeasts as microbial agents for wines produced from non-Vitis vinifera grapes: A sensometric approach. Part I: BRS Núbia - Alves, Danieli Cristina [UNESP]; Del Bianchi, Vanildo Luiz [UNESP]; de Castilhos, Maurício Bonatto Machado (FapUNIFESP (SciELO), 2024)
Wines are produced from Vitis vinifera or American/hybrid grapes as a result of alcoholic fermentation and this bioprocess is modulated by yeasts of the Saccharomyces or non-Saccharomyces species. This study aimed at characterizing the chemical and sensory acceptance profiles of wines produced from BRS Núbia hybrid grapes with the classic yeast Saccharomyces cerevisiae (SC), and alternative yeasts Saccharomyces bayanus (SB) and Saccharomyces uvarum (SU). The wines produced using the same winemaking protocol were evaluated using the physicochemical parameters of total acidity, volatile acidity, total dry extract, reducing sugars, alcohol content, total phenolic content, color indices and the sensory acceptance method. All the physicochemical parameters evaluated were in accordance with the legislation. The SC wine sample showed greater acceptance of appearance and body due to its high color intensity, reducing sugar and total phenolic content. The SU wine sample was related to the physicochemical parameters of acidity (total and volatile), alcohol content, dry extract and CIELab parameters, showing higher acceptance for aroma, flavor, overall acceptance and purchase intention. The SB wine showed no relationship with any physicochemical property or sensory acceptance attribute. The SU yeast showed potential in producing wines with great acceptance by Brazilian consumers, considered an alternative yeast that can be used for the production of hybrid grape wines.
Leveduras alternativas como agentes microbianos para vinhos produzidos a partir de uvas não-Vitis vinifera: Uma abordagem sensométrica. Parte 1: BRS Núbia
Keywords: hybrid grape; red wine; Saccharomyces bayanus; Saccharomyces uvarum; sensory profile